Grammar and composition (New York, 2001)
This is a high school textbook focusing on english writing. The contents are devided into three section Composition, Grammar, usage, and mechanics and Resources and skills.
Keywords: English language,English language,Anh ngữ; Composition and exercises,Study and teaching (Secondary),Grammar,Study and teaching (Secondary),Ngữ pháp,Dạy và học